2016
DOI: 10.17796/1053-4628-40.5.361
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Revascularization of Necrotic Permanent Teeth with Immature Apices

Abstract: Clinical and radiographic evidence showed successful revascularization treatments of immature necrotic permanent teeth with apical periodontitis. More studies are necessary to understand the underlying mechanisms and to perform histopathology of the pulp space contents after revascularization procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…In the aforementioned cases, great damage to periodontal ligament, which was shown to be a reason for root resorption, is very unlikely, which explains our high rate of resorption compared to other case reports. Moreover, re-implanted teeth have a higher risk of Hertwig's epithelial root sheath (HERS) or apical papilla injury [13,52], which are described as the most important elements to determine the continuing of root development after a severe trauma [14,52,53]. Thus, traumatized teeth, especially avulsed teeth, are less likely to complete root development after revascularization than teeth with necrotic pulp caused by caries [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the aforementioned cases, great damage to periodontal ligament, which was shown to be a reason for root resorption, is very unlikely, which explains our high rate of resorption compared to other case reports. Moreover, re-implanted teeth have a higher risk of Hertwig's epithelial root sheath (HERS) or apical papilla injury [13,52], which are described as the most important elements to determine the continuing of root development after a severe trauma [14,52,53]. Thus, traumatized teeth, especially avulsed teeth, are less likely to complete root development after revascularization than teeth with necrotic pulp caused by caries [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, many case reports and case series viewed revascularization very positively, as the studies observed an increase in root length and dentin wall thickness [ 9 , 12 – 14 , 16 , 19 ]. The discrepancies in our study can be explained based on the following issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, obtaining fresh blood clot is not always possible and there is enough evidence to support this drawback. 11,12 Although various biologically based scaffold materials like platelet-rich plasma or platelet-rich fibrin, and collagen have been used with successful results, each one documented with their own disadvantages. Therefore, there is a quest for the best approach which leads to the development of the amniotic membrane in the arena of tooth tissue engineering.…”
Section: Discussionmentioning
confidence: 99%